The Referrals of the Algerian dystopian reality as a common human through the narrative characters in the novel "Trollar Ladders" by Samir Kassimy: a forward-looking vision - Melghid, Doua Nahla; Terchak, Souad (Journal of Human Sciences, 2022)
The human common in the contemporary Algerian novelist text is remarkable, and the researchers have attached great importance to it, because of the dimensions it bears that refer to the lived reality not only within the national and local boundaries, but also because its issues rise to the ranks of the world, and among the writers whose speech was a founding message for the ideas of the common human literary Samir Qasimi, whose presentation was referred to the world, he contributed to blurring the images of the virtuous human illusion in life, through his novel “Troller’s Ladders”, which he referred us to the various worlds, their backgrounds and reflections that imposed the dystopian reality Which is not restricted to Algeria only, but rather a reflection of many countries in the world, relying in its depiction of the various manifestations of the human common on a unique, cynical, fantastical perspective.